A window onto the world of merchants: An analytical grid for interpreting notarial contracts in the seventeenth and eighteenth centuries - Cátia Antunes (The Journal of European Economic History (JEEH), 2023)
Early Modern historians have long been fascinated by the mercantile world of the late medieval and early modern periods. The reason for their fascination can be ascribed to the wealth, cosmopolitism, social capital and political clout that many of these merchants (mostly men) projected onto their compatriots at the time and continue to project onto historians today. However, there are obstacles to entering the world of early modern merchants as sources for certain geographical areas are abundant, but rather scarce for others. Urbanized regions like the Italian Peninsula, the Low Countries or the former Hansa towns seem to offer better insights into the world of merchants than areas plagued by natural disasters or where different mercantile practices prevailed, such as in the Eastern Mediterranean or the Iberian Peninsula (with a significant difference between the sources to be found for Portugal and those available for Spain). This article proposes an analytical grid for the interpretation of notarial contracts worldwide (based on the experience of Amsterdam) in order to better understand the social intricacies that framed the world of premodern merchants.
Keywords: 330; Merchants; legal professions; legal advice; foreign trade; trade history; economic history; Hanseatic League; Spain; Portugal; Italy; Netherlands; Kaufleute; Rechtsberufe; Rechtsberatung; Außenhandel; Handelsgeschichte; Wirtschaftsgeschichte; Hanse; Spanien; Portugal; Italien; Niederlande